Enhancing Global Security through EU Public Diplomacy: Innovative Strategies for Multilateral Engagement in Times of Crisis - Shrivastava, Vikramaditya (HAPSc Policy Briefs Series, 2025)
Recent global crises—from Brexit and the COVID-19 pandemic to the ongoing Russia–Ukraine conflict—have highlighted both vulnerabilities in and opportunities for the European Union’s (EU) crisis management and public diplomacy. This policy brief examines how refining and strategically deploying public diplomacy during times of uncertainty can reinforce internal security while enhancing the EU’s multilateral engagement on the global stage. Through a critical analysis of past crises, case studies and comparative insights, this brief offers evidence-based, actionable recommendations aimed at improving the EU’s diplomatic response. Key initiatives include establishing a unified crisis communication protocol, expanding multilateral outreach, investing in strategic communication training and formally integrating public diplomacy into the EU’s security policy. These recommendations are designed to render the EU a more integral, cohesive and effective global actor.